Faktor Peybebab Anak Menjadi Korban Pencabulan Sesama Jenis Di Bone Bolango - Lessy, Andi Azrial Oppier; Puluhulawa, Fenty U; Achir, Nurvaria (CV. ITTC INDONESIA, 2022)
This study aims to find out what are the factors that cause children to become victims of same-sex abuse in Bone Bolango and how the law protects victims of same-sex abuse by the PPA unit of the Bone Bolango Police. This study uses empirical legal research methods which are conducted by collecting data through observation and interviews. The results of the study show that children are vulnerable to becoming victims of crime. Children are often considered to be sexual objects by adults in society, so children are seen as victims who are weak and easy to be controlled by adults, especially in committing crimes. Factors that cause children to become victims of sexual abuse are due to internal factors: personality, faith; and external factors: family supervision, community environment, technology and mass media. The legal protection provided by the PPA Unit of the Bone Bolango Police to children as victims of same-sex abuse is in the form of protection for the victim's safety, providing psychosocial rehabilitation medical assistance and counseling services, providing legal assistance, providing information in terms of the convict being released, and outreach. However, the provision of legal protection is still not optimal for victims so that victims do not feel safe and recover from their trauma. Counseling and outreach provided by the police and P2TP2A should be carried out in a comprehensive manner, on target and able to utilize existing technology, this is to prevent victims of criminal acts of same-sex obscenity underage, and can increase the understanding and legal awareness of the community towards human rights. -the rights of victims and guarantees of legal protection for victims of criminal acts of same-sex obscenity to minors. Every member of society, especially parents and adolescents, needs to be given adequate understanding of the risks and consequences of crimes of sexual abuse against children. In addition, parents/families are expected to be able to be actively involved in supervising the activities of their children when they are outside the home, and to provide extra supervision to family members wisely so that they do not become perpetrators or victims of same-sex obscenity crimes.